The influence of seasonal migration on range size in temperate North American passerines. Issue 8 (8th May 2020) - Pegan, Teresa M.; Winger, Benjamin M.
Abstract : Seasonal migration has been alternately proposed to promote geographic range size in some contexts and to constrain it in others, but it remains unclear if migratory behavior has a general effect on range size. Because migration involves movement, most hypotheses about the relationship between migration and range size invoke an influence of migration on the process of dispersal‐mediated range expansion. Intuitively, a positive relationship between migratory behavior and dispersal ability could bolster range expansion among migratory species, yet some biogeographic patterns suggest that long‐distance migration may instead impede range expansion, especially in the temperate zone. We conducted a comparative analysis of the relationship between migratory behavior and range size by testing the effect of migratory status, migration distance and morphological dispersal ability on breeding range size among all temperate North American passerines. Further, we assessed whether these traits affect range expansion into suitable habitat by analyzing their relationship with range filling (the proportion of climatically‐suitable area occupied, or 'filled' by a species). Contrary to previous studies, we found migration and dispersal ability to be poor predictors of range size and range filling in North America. Rather, most variation in range size is explained by latitude. Our results suggest that migratory behavior does not affect range size within the scale of a continent, and furthermore, that temperate North American passerines' breeding ranges are not influenced by their dispersal abilities. To better understand why migratory behavior appears to promote range size in some contexts and constrain it in others, future studies should investigate how migratory behavior affects dispersal at the individual level, as well as the relationship between the evolution of migratory behavior and the breadth of species' climatic niches.